Randomized phase III PITCAP trial and meta-analysis of induction chemotherapy followed by thoracic irradiation with or without concurrent taxane-based chemotherapy in locally advanced NSCLC. (October 2016) - Ardizzoni, Andrea; Tiseo, Marcello; Boni, Luca; Di Maio, Massimo; Buffoni, Lucio; Belvedere, Ornella; Grossi, Francesco; D'Alessandro, Vito; de Marinis, Filippo; Barbera, Santi; Caroti, Cinzia; Favaretto, Adolfo; et al.
Highlights: Chemo-radiotherapy is standard of care in the unresectable stage III NSCLC. We performed a multicenter phase III trial and a literature-based meta-analysis. Addition of taxane to thoracic radiotherapy after induction chemotherapy was studied. The results do not support a clinically meaningful benefit on survival. Abstract: Background: Chemo-radiotherapy is standard of care in the treatment of unresectable stage III NSCLC. We aimed at assessing whether the addition of concurrent taxane-chemotherapy to thoracic irradiation following chemotherapy was able to improve treatment outcome. Material and methods: In PITCAP trial, patients with unresectable stage III NSCLC were randomized to receive 2 cycles of platinum-paclitaxel followed by 60–61.2 Gy thoracic irradiation (control arm) or by same radiotherapy with concomitant weekly paclitaxel (experimental arm). A literature-based meta-analysis including all studies with same design was also performed. Results: At the time of the second interim analysis, when 151 patients were randomized, accrual was terminated. With a median follow-up of 6.1 years, median survival was 13.2 vs 15.1 months, with a 3-year survival rate of 19.5 vs 21.2% in the control and experimental arm, respectively (HR: 0.97; 95% CI 0.69–1.36; p = 0.845). Treatment toxicity was manageable in both arms. The meta-analysis of 5 trials (n = 866) confirmed the lack of a meaningful effect on 1-year overall survival of a taxane added concurrently to radiotherapy. Conclusions: These results do not support a meaningful survival benefit with the addition of single agent taxane given concurrently to radiotherapy after platinum-based induction in locally advanced NSCLC.